2018
DOI: 10.1080/00107514.2018.1467648
|View full text |Cite
|
Sign up to set email alerts
|

Scientific discovery with the James Webb Space Telescope

Abstract: For the past 400 years, astronomers have sought to observe and interpret the Universe by building more powerful telescopes. These incredible instruments extend the capabilities of one of our most important senses, sight, towards new limits such as increased sensitivity and resolution, new dimensions such as exploration of wavelengths across the full electromagnetic spectrum, new information content such as analysis through spectroscopy, and new cadences such as rapid time-series views of the variable sky. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 303 publications
0
47
0
1
Order By: Relevance
“…With the upcoming large sky surveys and telescope missions, such as the James Webb Space Telescope (JWST; Gardner et al 2006;Kalirai 2018), the MeerKAT Karoo Array Telescope HI Surveys (Holwerda et al 2012), the Australian Square Kilometre Array Pathfinder HI surveys (Johnston et al 2007(Johnston et al , 2008, the Multi-Unit Spectroscopic Explorer (MUSE; Bacon et al 2010), the K-band Multi-Object Spectrograph (KMOS; Wisnioski et al 2015) surveys, and Atacama Large Millimeter/submillimeter Array (ALMA) future surveys, we expect to be able to study ring galaxies at higher redshifts and larger volumes due to their deep and large sky coverage. Through these surveys, we will also be able to test the simulation predictions and probe both the gas-phase pressure and the metallicity in these galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…With the upcoming large sky surveys and telescope missions, such as the James Webb Space Telescope (JWST; Gardner et al 2006;Kalirai 2018), the MeerKAT Karoo Array Telescope HI Surveys (Holwerda et al 2012), the Australian Square Kilometre Array Pathfinder HI surveys (Johnston et al 2007(Johnston et al , 2008, the Multi-Unit Spectroscopic Explorer (MUSE; Bacon et al 2010), the K-band Multi-Object Spectrograph (KMOS; Wisnioski et al 2015) surveys, and Atacama Large Millimeter/submillimeter Array (ALMA) future surveys, we expect to be able to study ring galaxies at higher redshifts and larger volumes due to their deep and large sky coverage. Through these surveys, we will also be able to test the simulation predictions and probe both the gas-phase pressure and the metallicity in these galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…They found that these objects could be observed today even by 8 − 10 m telescopes on the ground, primarily because of their high surface temperatures (20,000 -30,000 K), larger masses (up to 10 7 M ⊙ ) and longer lives (up to 10 7 yr; see also recent reviews by Freese et al 2016;Banik et al 2019). Most recently, Surace et al (2018) calculated spectra for cool, red SMSs and found that some will be visible to the James Webb Space Telescope (JWST; Gardner et al 2006;Kalirai 2018) at z 20 and at z ∼ 10 -12 to Euclid (Laureijs et al 2011) and the Wide-Field Infrared Space Telescope (WFIRST; Spergel et al 2015) if they are gravitationally lensed. Hartwig et al (2018) also found that the relics of such stars would be uniquely identifiable with the gravitational wave detector LISA at z > 15 if they form in binaries.…”
Section: Introductionmentioning
confidence: 99%
“…The launch of the James Webb Space Telescope (JWST) in 2021 will pave the way for an increased understanding of the z > 7 Universe (e.g. Gardner et al 2006;Kalirai 2018). JWST, with its 6.5m diameter mirror, will make observations from the optical to mid-infrared (0.6 µm to 30 µm) to probe the earliest galaxies and the stars contained within them.…”
mentioning
confidence: 99%